Mature Cystic Retroperitoneal Teratoma with Well Differentiated Renal Elements: Relation to Spinal Dysraphism - Sinha, Anand; Sabharwal, Arvind; Yadav, Nandini; Gupta, R. K.; Patir, Rana (European Journal of Pediatric Surgery Reports, 2014)
Retroperitoneum is a relatively uncommon site for pediatric teratomas. Rarely, such tumors can have an intraspinal extension and few cases of retroperitoneal teratomas associated with spinal dysraphism have been reported. Teratomas consist of tissues arising from all three embryonic layers. However, mature renal tissues in the form of glomeruli and tubules are sparingly found in teratomas. A 15-day-old female presented with spina bifida occulta and on evaluation a cystic presacral mass was detected. Intraoperatively the cyst was found densely adherent to the hemivertebrae but not entering the spinal canal. Histopathological examination confirmed a mature cystic teratoma but also demonstrated presence of mature renal elements in the cyst wall. The teratomas lying in proximity to spine and associated with spinal dysraphism are likely to contain mature renal tissues or even nephroblastic elements. It supports the dysembryogenic model of origin of intradural teratomas from native progenitor cells rather than aberrantly migrated germ cells.
Keywords: retroperitoneal teratoma; mature renal elements; intraspinal extension